2000
DOI: 10.1034/j.1399-3038.2000.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Wheezing in early life and asthma at school age: Predictors of symptom persistence

Abstract: Early childhood wheezing is associated with asthma later in life. However, the high spontaneous recovery rate and the lack of firm predictors for persistence of wheezing complicates the development of evidence-based guidelines for long-term management of wheezy infants and toddlers. Our aim was to define variables that could be used to identify wheezy individuals younger than 3 years of age who would continue to be symptomatic at school age. The method used was a questionnaire-based cross-sectional survey of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 23 publications
2
20
1
3
Order By: Relevance
“…The present findings add to those of CSONKA et al [12] who retrospectively looked at risk factors for wheezing persistence in their study group, and confirm the importance of heredity towards the persistent asthmatic phenotype suggested by LONDON et al [13]. These results are also consistent with findings emerging from the Multicentre Asthma Study (MAS) [14] that identified an interaction of persistent atopic sensitisation in childhood and parental atopy/asthma as being associated with childhood asthma development.…”
Section: Discussionsupporting
confidence: 82%
“…The present findings add to those of CSONKA et al [12] who retrospectively looked at risk factors for wheezing persistence in their study group, and confirm the importance of heredity towards the persistent asthmatic phenotype suggested by LONDON et al [13]. These results are also consistent with findings emerging from the Multicentre Asthma Study (MAS) [14] that identified an interaction of persistent atopic sensitisation in childhood and parental atopy/asthma as being associated with childhood asthma development.…”
Section: Discussionsupporting
confidence: 82%
“…Mikalsen et al, in a population of 93 children under 2 years of age hospitalized for bronchiolitis during their first year of life, reported that although recurrent wheeze was the only independent predictor of asthma at the age of 11 years (OR=7.2; 95% CI: 1.3–41.6; p =0.015), combining recurrent wheeze with either parental atopy or parental asthma improved specificity (>80), positive likelihood ratio (LR) (>3), and positive posttest probability (50%), rendering that combination more appropriate for the prediction of later ocurrence of asthma 19. Csonka et al reported in a population of 1816 children younger than 3 years of age that family history of asthma (defined as children with a biological parent or sibling with known asthma) was independently associated (OR=1.9; 95% CI: 1.3–2.8; p =0.001) with symptom persistence up to school age 20. Finally, Neuman et al aimed to identify clinical risk factors for current asthma at 8 years of age in 823 Swedish infants who wheezed during the first 2 years of life in a population-based setting.…”
Section: Resultsmentioning
confidence: 99%
“…Pescatore et al proposed eczema as one of the ten predictors (OR=1.52; p <0.001) included in their tool for predicting asthma 18. Csonka et al identified itchy rash as an independent predictor of symptom persistence up to school age in a population of children younger than 3 years with recurrent wheezing (OR=2.2; 95% CI: 1.6–3.2; p <0.001) 20. Reijonen et al followed a population of 89 infants under 2 years of age hospitalized for respiratory infections associated with wheezing in order to assess the development of asthma 3 years after hospitalization.…”
Section: Resultsmentioning
confidence: 99%
“…25 There are also studies indicating that asthma in combination with any other allergic manifestation in early life increases the risk of having the disease over many decades. 26 Since there was a preventive effect of exclusive breast feeding on atopic dermatitis as well as on the risk of having three or more allergic manifestations up to 2 years of age, the effects seen for breast feeding might be long lasting.…”
Section: Tablementioning
confidence: 99%